Built-in electric field enabled in carbon-doped Bi3O4Br nanocrystals for excellent photodegradation of PAHs - Jing Ji; Xianbo Sun; Weiyu He; Yongdi Liu; Duan, Jun; Liu, Wen; Long D. Nghiem; Qilin Wang; Cai, Zhengqing (Separation and Purification Technology, 2022)
A new type of solar active carbon-doped Bi3O4Br catalyst was synthesized by combining hydrothermal and post-thermal treatment. The activity of the material under sunlight and visible light was 3.3 times and 2.7 times that of Bi3O4Br, respectively. The C-doping on Bi3O4Br nanosheets increased the built-in electric field strength, thus significantly promoted the migration of charge carriers and enhanced the photocatalytic activity. In addition, replacing Br with C with a smaller atomic radius can shorten the interlayer spacing, which is beneficial to carrier separation. Experiments showed that the doping of C shortened the semiconductor band gap by 9.8% and expanded the absorption range of visible light. Among the photogenerated reactive species, h+ played a major role in the degradation of 1-methylpyrene (a typical polycyclic aromatic hydrocarbons), followed by O2∙- and •OH. Based on intermediate analysis and DFT calculation, we proposed the degradation mechanism and pathways. Quantitative structure–activity relationship (QSAR) analysis showed that some toxic intermediates were produced during the photocatalysis process, but the overall environmental risk was greatly reduced. This work provides new perspective for understanding non-metallic doping in semiconductor photocatalysts to enhance the built-in electric field, and this technology can be extended to other semiconductor materials.
Keywords: C-BiOBr; Electron-hole pair; Internal electric field; pahs; Photocatalytic